Analysis Of Pig Husbandry Practices In Semi- Arid Region Of Tamil Nadu - Ramesh, V.; Muralidharan , J.; Kumar , V. Ramesh Saravana (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
The present study was carried out to analyse the pig husbandry practices in semi- arid region of Tamil Nadu. The study revealed that, 95.00 per cent of farmers reared the pigs in shed covered with asbestos sheet (53.83 per cent) followed by thatches (34.64 per cent) on concrete flooring (92.28 per cent). The majority of the farmers (76.92 per cent) maintaining Large White Yorkshire pigs and followed natural service using boars. The farmers followed stall feeding and 50 % of the farmers fed swill feeding along with poultry offal waste with small quantity of own mix concentrate feed. Majority of the farmers (50 % ) vaccinated their pigs against both swine fever and FMD and 19.23 per cent of the farmers did not give any vaccination. 61.54 % farmers followed deworming using allopathic medicine. Similarly, only 65 per cent of the farmers protected their piglets against piglet anemia with iron injection and 32.5 % of them used ectoparasitic drugs in their farms. The farmers followed weaning at 2 months of age and castration of male piglets at 2 to 3 weeks of age. Pigs were marketed at 8 to 9 months of age when they attained the body weight of 90 to 100 kg at the rate of Rs.90 to 95 per kg live weight.